La aproximación ideológica de Sanz del Río al liberalismo progresista y su primera polémica con la prensa tradicionalista - Orden Jiménez, Rafael V. (Anales del Seminario de Historia de la Filosofía, 2005)
Julián Sanz del Río, founder of the philosophical movement of Spanish krausism, evolved politically from the moderate to the progressive liberalism between 1844 and 1854. His moderate friends ignored this occurrence, and supported him, until his reviews of two french books published in the Gaceta de Madrid, denounced for heterodoxy by the traditionalist press and then by the Bishops from Barcelona and Zamora, revealed to them his true true political positions and his anticlericalism.